Pengaruh Dana Pihak Ketiga, Capital Adequacy Ratio, dan Return On Asset Terhadap Penyaluran Kredit Pada Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020 - Ghea Ayu Noviarvanty; Siti Aminah (Serat Acitya, 2022)
This study aimed to determine the effect of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), and Return On Assets (ROA) on credit distribution at banking sector listed in Indonesian Stock Echange for the 2018-2020 period. The population used in this study is all financial statements of commercial banks listed on the Indonesia Stock Exchange during 2018 - 2020, and the size of the sample used is 87 observational data, with the sampling technique using the census method that data was secondary data. The method of data collection was documentation. The data analysis technique used was multiple linear regression analysis. The results showed that Third Party Funds had a significant positive effect on lending, the Capital Adequacy Ratio had an insignificant negative effect on lending, and Return On Asser had a positive but not significant effect on lending. The value of the coefficient of determination is 0.702, meaning that the variables of Third Party Funds, Capital Adequacy Ratio and Return On Assets can explain the variation in lending variables of 70.2%.